Lag-Screw Osteosynthesis in Thoracolumbar Pincer Fractures. Issue 7 (September 2021) - Auerswald, Marc; Messer-Hannemann, Philipp; Sellenschloh, Kay; Wahlefeld, Jan; Püschel, Klaus; Araujo, Sven Hirschfeld; Morlock, Michael M.; Schulz, Arndt P.; Huber, Gerd
Study Design: Biomechanical. Objective: This study evaluates the biomechanical properties of lag-screws used in vertebral pincer fractures at the thoracolumbar junction. Methods: Pincer fractures were created in 18 bisegmental human specimens. The specimens were assigned to three groups depending on their treatment perspective, either bolted, with the thread positioned in the cortical or cancellous bone, or control. The specimens were mounted in a servo-hydraulic testing machine and loaded with a 500 N follower load. They were consecutively tested in 3 different conditions: intact, fractured, and bolted/control. For each condition 10 cycles in extension/flexion, torsion, and lateral bending were applied. After each tested condition, a computed tomography (CT) scan was performed. Finally, an extension/flexion fatigue loading was applied to all specimens. Results: Biomechanical results revealed a nonsignificant increase in stiffness in extension/flexion of the fractured specimens compared with the intact ones. For lateral bending and torsion, the stiffness was significantly lower. Compared with the fractured specimens, no changes in stiffness due to bolting were discovered. CT scans showed an increasing fracture gap during axial loading both in extension/flexion, torsion, and lateral bending in the control specimens. In bolted specimens, the anterior fragment was approximated, and the fracture gap nullified. This refers to both the cortical and the cancellous thread positions. Conclusion: The results of this study concerning the effect of lag-screws on pincer fractures appear promising. Though there was little effect on stiffness, CT scans reveal a bony contact in the bolted specimens, which is a requirement for bony healing.